Kepemimpinan Visioner Kepala Sekolah dalam Meningkatkan Mutu Manajemen Pendidikan di SMP Negeri 6 Kuala Tungkal - Nijam Nijam (JMiE (Journal of Management in Education), 2024)
Learning is a fundamental task in education aimed at supporting and improving students’ learning quality. This study seeks to examine the role of the principal as a visionary leader in enhancing educational management quality at SMP Negeri 6 Kuala Tungkal. The research employed a qualitative approach with data collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing with verification. The findings reveal that visionary leadership has been implemented in the school but has not yet reached its optimal level. The challenges include limited opportunities for teachers to attend training programs, the presence of teachers whose academic background is not in education, and insufficient facilities and infrastructure to support effective learning. Therefore, the principal as a visionary leader needs to take initiatives such as recruiting qualified teachers with appropriate academic backgrounds, strengthening centers of excellence, and improving facilities and infrastructure to ensure more effective educational management.